Islam and Western Europe in contemporary times - Музыкина, Е. В. (Journal of Oriental Studies, 2018)
It seems that today Islam has become an integral part of Western Europe. Citizens of Great Britain, France, Germany and other countries of the European Union consider themselves Muslims. However, this situation did not happen immediately. For half a century, Muslims who were coming from the former colonies to the flourishing metropolis had to adapt, adjust and get changed. The article examines the demographic, political and socio-cultural changes that occurred during the period, as well as the results they led to. If the main goal for the first generation of migrants was to gain a foothold in the new territories, then nowadays the third and fourth generations of Muslim migrants have to defend different rights and values.